Pore structure characterization for coal measure shales of the Xiashihezi Formation in the Sunan Syncline block, southern North China basin - Qian Wang; Qian Wang; Xianbo Su; Xianbo Su; Xianbo Su; Xianbo Su; Yi Jin; Yi Jin; Peihong Chen; Weizhong Zhao; Weizhong Zhao; Shiyao Yu (Frontiers in Earth Science, 2022)
To characterize the coal measure shale pore structure of the Xiashihezi Formation in the Sunan Syncline block, a series of experiments were conducted. Results show that the main components of the shales are clay minerals and quartz, and organic matter, fluid escaping, interlayer, intercrystalline and interparticle pores are well-developed. The shale pore specific surface area (SSA) is concentrated in the pores with the size of <50 nm and is significantly higher in the pores with the size of < 5 nm, indicating that these pores have an important effect on gas adsorption. The shale pore volume is mainly concentrated near the pore size of 10 nm, followed by 10,000–100,000 nm, indicating that in addition to the fractures, the matrix pores with a size of about 10 nm contribute the most to pore volume and free gas accumulation. The volume and SSA of the micropore, small pore, and mesopore increase with the TOC content when it is lower than 6%, leading to higher porosity and total pore SSA of the shales. However, this positive correlation disappears under the compaction effect when the TOC content is higher than 6%. The clay mineral content has negative correlations with the volume and SSA of the mesopore and macropore under the compaction and pore blockage effects, but it correlates poorly with those of the micropore and small pore, causing a decrease in the shale porosity as it increases, while the brittle mineral can promote mesopore and macropore development and is conducive to micropore and small pore maintenance when its content is higher than 45%. As a result, the shale porosity tends to increase with the brittle mineral content. This study is helpful in clarifying the coal measure shale gas enrichment law in the block and in providing fundamental support for coal measure gas efficient development.